Third dose of anti-SARS-CoV-2 vaccine for patients with cancer: Should humoral responses be monitored? A position article. (February 2022) - Barrière, Jérôme; Carles, Michel; Audigier-Valette, Clarisse; Re, Daniel; Adjtoutah, Zoubir; Seitz-Polski, Barbara; Gounant, Valérie; Descamps, Diane; Zalcman, Gérard
Abstract: Taking into account higher risk of severe coronavirus disease 2019 or death among patients with cancer, as well as impaired immunogenicity after anti-SARS-CoV-2 vaccines, in addition to waning immunity, booster dosing appears mandatory in this patient population. This review sought to provide reasonable evidence so as to assist oncologists in their daily practice, helping them decide when an anti-SARS-Cov2 antibody (Ab) dosage should be scheduled after a full two-dose vaccination and, if necessary, propose an early third dose (D3). Such D3 could apply to non-responder patients with anti-Spike (S) Abs titres <40 binding Ab unit (BAU)/mL. For lowresponder patients with anti-S Ab titres between 40 BAU/mL and 100/260 BAU/mL (suggested area of uncertainty), an early D3 may similarly be proposed. Nevertheless, this D3 could be administered in a less urgent manner, taking into account associated comorbidities and regional epidemic incidence rates. This latter strategy may comprise a monthly dosage of anti-S titres so as to better assess the kinetics of waning immunity. For responder patients with anti-S titres above 260 BAU/mL, we suggest to follow the recommendations outlined for the general population. Given this context, patients with anti-S titres above 1000 BAU/mL should be given the possibility to undergo anti-S titre control after three months, designed to assess rapid humoral waning immunity. We strongly recommend that patients with cancer be included into observational serological monitoring studies or clinical trials that are dedicated to severe immunocompromised patients without any humoral seroconversion after D3. Highlights: Patients with cancer are at risk of low median anti-Spike (S) antibody (Abs) titre. Early third dose (D3) of anti-SARS-CoV-2 vaccine should be performed for poor responders. We recommend anti-S Ab dosing at 3–4weeks after full vaccination. An early D3 should be given if titre <40 binding Ab unit/mL or above in case of high incidence. We encourage vaccine dedicated clinical trials for patients with cancer.